Potato late blight control based on the Blitecast forecast system on the Rio Grande do Sul Plateau, Brazil - Gabriele Maito; Mateus Possebon Bortoluzzi; Samuel Zottis Dal Magro; Laura Valentina Caus Maldaner (Ciência Rural)
ABSTRACT: Potato (Solanum tuberosum L.) is an increasingly important source of food, rural employment, and financial income, contributing to the social stabilization of rural areas, especially in developing countries. However, this crop is very sensitive to diseases, which drastically affect yield, in addition to increasing production costs for their control and the risk of environmental contamination. This study evaluated the control of late blight (Phytophthora infestans) in potato cv. Ágata based on the Blitecast disease forecast system and tuber yield in two growing seasons. The experiments were conducted in the spring of 2022 and autumn of 2023 in the municipality of Passo Fundo. Different accumulated severity values (SV) were calculated by the Blitecast model, which constituted the treatments SV 18, SV 24 and SV 30, in addition to a weekly treatment and a control without application. The experimental design consisted of randomized blocks with four replications, in which each plot had five rows of plants measuring 3 m in length. Late blight severity and the final tuber yield were evaluated. The use of the Blitecast forecast system to control potato late blight allows for a reduction in the number of fungicide applications without affecting the final tuber yield. The forecast system should be used as a tool for the integrated management of potato diseases.